1989
DOI: 10.1346/ccmn.1989.0370504
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Isotope Measurements of Albite-Quartz-Zeolite Mineral Assemblages, Hokonui Hills, Southland, New Zealand

Abstract: Abstract--The oxygen isotopes of albite, quartz, and zeolites from the Hokonui Hills, New Zealand, constrain crystallization temperatures and the type of pore fluids present during diagenesis. A section of altered vitric tufts in this region contains an extremely sharp reaction boundary between a heulanditechlorite assemblage containing fresh detrital plagiodase and a laumontite-albite-quartz assemblage. A laumontite vein follows the local joint pattern and forms the reaction boundary, suggesting that laumonti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Jointcontrolled replacement of heulandite by laumontite together with microcrystalline quartz, K-feldspar and albite has been described by Boles & Coombs (1975) and Stallard & Boles (1989) for one of the stratigraphically lowest Occurrences of heulandite. Clastic plagioclase is simultaneously albitized.…”
Section: Replacement Of Heulandite By Bumontitementioning
confidence: 86%
See 1 more Smart Citation
“…Jointcontrolled replacement of heulandite by laumontite together with microcrystalline quartz, K-feldspar and albite has been described by Boles & Coombs (1975) and Stallard & Boles (1989) for one of the stratigraphically lowest Occurrences of heulandite. Clastic plagioclase is simultaneously albitized.…”
Section: Replacement Of Heulandite By Bumontitementioning
confidence: 86%
“…Stallard & Boles (1989) interpret oxygen isotope data on quartz-albite pairs as constraining the alteration to a temperature in the range 145-170" C. The quartz-laumontite pair suggests a temperature in the range 139-162°C. Based on their position in the stratigraphic section, however, these rocks are believed to have been exposed to a maximum temperature of up to 225°C when at their maximum burial, which probably exceeded 9 km.…”
Section: Replacement Of Heulandite By Bumontitementioning
confidence: 97%
“…In the absence of experimental data, Stallard and Boles (1989) developed a semiempirical expression relating zeolite framework-water fractionation to the Si/Al ratio of the Karlsson and Clayton (1990b); 2: Feng and Savin (1993b); 3: Noto and Kusakabe (1997a).…”
Section: Figurementioning
confidence: 99%
“…For example, their predicted analcime (or wairakite) fractionation is too low by 1‰ and 1.8‰ at 250°C and 25°C, respectively. The semi-empirical expression of Stallard and Boles (1989) can therefore be used to estimate isotopic fractionation for zeolites where experimental data are lacking. Another semi-empirical approach is based on bond counting.…”
Section: Figurementioning
confidence: 99%
“…Diffusively migrating fluids may have been responsible. Stallard & Boles (1989) and Boles (1991) showed that in the Southland Syncline substantial mineralogical reconstitution has taken place, not at the maximum depths of burial and temperatures to which the sediments were subjected, but at lower temperatures related to post-dating folding and uplift. Similar effects may be anticipated in the Willsher Group with low temperatures further impeding the approach to equilibrium mineral assemblages.…”
Section: Diagenesis Very Low-grade Metamorphism Maturationmentioning
confidence: 99%